EFFECTIVE MARKETING STRATEGIES FOR MSMEs DURING RAMADAN IN INDONESIA - Sutrisno Sutrisno; Abu Muna Almaududi Ausat; Riko Mersandro Permana; Sonny Santosa (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
The month of Ramadan is an important moment for Muslim communities in Indonesia which is characterised by fasting for a whole month. In addition to having high religious value, the month of Ramadan is also a moment to look forward to shopping and doing business for MSMEs. In Indonesia, MSMEs are one of the largest sectors and contribute significantly to the economy. However, MSMEs still experience many obstacles in marketing their products, especially during the month of Ramadan. Therefore, research is needed on effective marketing strategies for MSMEs during the month of Ramadan in Indonesia. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The results of this study concluded that in preparing an effective marketing strategy, MSMEs should consider online presence, special offers, events or competitions, improving product and service quality, collaborating with other businesses, paying attention to customer needs, and halal products. MSMEs should also monitor the performance of their marketing campaigns, consider ethics in marketing, and conduct sufficient research and analysis before designing their strategies.